2021
DOI: 10.1590/s1980-220x2020007403723
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the vaccination status of older adults

Abstract: Objective: To describe the sociodemographic characteristics, functional capacity and vaccination status of older adults, and to verify the factors associated with the incomplete vaccination status and the absence of the vaccination card. Method: Cross-sectional and analytical study conducted with older adults living in the city of Uberaba (MG). The following analyzes were carried out: descriptive, bivariate and multinomial logistic regression (p<0.05). Results: A total of 576 older adults participated. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
2
1
0
3
Order By: Relevance
“…Regarding sociodemographic characteristics, the study found that elderly females had a higher prevalence of vaccination compared to their male counterparts, which is consistent with previous studies 8,13,14,[18][19][20][21] . However, a study carried out in Campinas-SP found a higher prevalence of vaccination against influenza in men 9 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Regarding sociodemographic characteristics, the study found that elderly females had a higher prevalence of vaccination compared to their male counterparts, which is consistent with previous studies 8,13,14,[18][19][20][21] . However, a study carried out in Campinas-SP found a higher prevalence of vaccination against influenza in men 9 .…”
Section: Discussionsupporting
confidence: 91%
“…The study identified a higher prevalence of influenza vaccination among elderly people who live at home with a spouse or partner, a finding that supports the association identified by a previous Brazilian study linking living alone with incomplete vaccination status among elderly people 19 . This suggests that elderly people with social support are more likely to prioritize their health care.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Nesse sentido, um estudo realizado com 576 pessoas idosas de Uberaba, Minas Gerais, com o objetivo de descrever as características sociodemográficas, a capacidade funcional e a situação vacinal dos participantes e verificar os fatores associados à situação vacinal incompleta e a ausência do cartão de vacinas, identificou que o acesso aos serviços de saúde é uma estratégia para intensificar a vacinação nesse grupo. No entanto, inquéritos nacionais e internacionais constatam falta de adesão a essa prática de saúde por esses indivíduos, apesar de a vacinação ser essencial para minimizar os riscos de adoecimento 32 .…”
Section: Atuação Da Equipe De Saúde Na Promoção Da Qualidade De Vida ...unclassified
“…É de comum conhecimento que a maioria dos indivíduos alcança essa faixa com alguma comorbidade, para além da senescência. Assim, salienta-se que a imunosenescência é uma alteração conjunta das células do sistema imune que limitam sua resposta e que, devido ao avanço da idade, faz-se necessário buscar alternativas para contornar as dificuldades associadas ao envelhecimento --como a entrada da vacinação contra a Hepatite A no Plano Nacional de Imunização (PNI) dos Idosos, atualmente disponível apenas na rede particular de vacinação (Alves & Bueno, 2019;Brito et al, 2018;Ferreira et al, 2021). A cobertura vacinal de Hepatite A analisada foi no período de 2014 a 2021, devido à ausência de informação de dados no Data/SUS.…”
unclassified